Resource selection and connectivity reveal conservation challenges for reintroduced brown bears in the Italian Alps. (June 2015) - Peters, W.; Hebblewhite, M.; Cavedon, M.; Pedrotti, L.; Mustoni, A.; Zibordi, F.; Groff, C.; Zanin, M.; Cagnacci, F.
Highlights: Predicted brown bear habitat suitability matched current habitat use well overall. Orchards and shrubs were used more; mixed woods, conifers and pastures less. Only two potential corridors for eastward population expansion were identified. The Adige Valley is main constraint to larger scale population connectivity with Dinaric–Pindos populations. Abstract: Large carnivores are declining worldwide and few examples of successful reintroductions exist, because of their large home-ranges, low reproductive rates, and penchant for human–wildlife conflict that is the main cause of their decline. Moreover, few studies assess whether habitat suitability predicted before reintroduction, a critical evaluation step, matches post-reintroduction habitat selection. We examined habitat-related factors contributing to a successful brown bear ( Ursus arctos ) reintroduction in central Europe. Starting in 1999, 10 brown bears were translocated from Slovenia to Trentino in the Italian Alps, and this population has since grown by >10%/year. First, we estimated multi-scale resource selection functions (RSF) with GPS collar data and validated models with k-folds cross validation and external VHF data. Then, we used Kappa-statistics to compare our population-scale RSF with a habitat suitability model (HSM) developed to predict potential habitat before reintroduction. Lastly, we employed least-cost path (LCP) analyses integrating our within home-range scale RSF to define movement paths. Overall, the HSM predicted post-reintroduction habitat selection well in many areas, but bears used orchards and shrubs more, and mixed/conifer forests and pastures less than expected prior to reintroduction. Finally, we identified road crossings of predicted paths between preferred habitat patches. We found two potential crossings in the Adige Valley, likely the biggest constraint for the study population to expand eastward and impeding dispersal to/from the closest bear population (Dinaric–Pindos population). Increasing awareness for key brown bear habitats and corridors, especially in potential ecological traps within cultural landscapes, will be necessary for large carnivore conservation.